A long persistence phosphor tailored quasi-solid-state dye-sensitized solar cell that generates electricity in sunny and dark weathers. Issue 35 (18th April 2017) - Tang, Qunwei; Wang, Min; Wang, Zhongling; Sun, Weiyin; Shang, Ruoxu
Abstract : An all-weather quasi-solid-state dye-sensitized solar cell is built using a long persistence phosphor tailored mesoscopic TiO2 photoanode and a three-dimensional conducting polymer gel electrolyte. Abstract : An all-weather quasi-solid-state dye-sensitized solar cell is built using a long persistence phosphor tailored mesoscopic TiO2 photoanode and a three-dimensional conducting polymer gel electrolyte. The so-called all-weather solar cell yields a maximum efficiency of 28.7% in the dark, making a promising photovoltaic revolutionary for state-of-the-art photovoltaics.